2017
DOI: 10.1111/tri.13090
|View full text |Cite
|
Sign up to set email alerts
|

Routine haemostasis testing before transplanted kidney biopsy: a cohort study

Abstract: Summary Kidney biopsy can result in bleeding complications. Prebiopsy testing using bleeding time (BT) is controversial. New whole blood haemostasis tests, such as platelet function analyser‐100 (PFA‐100) and multiple electrode aggregometry (MEA), might perform better. We postulated that PFA‐100 would be suitable to replace BT prebiopsy. In 154 patients, transplanted kidney biopsies were performed after measurement of bleeding time, PFA‐100, MEA and mean platelet volume (MPV). Bleeding outcome (haemoglobin (Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…After the removal of duplicates, 5004 unique records were identified, of which 4814 records were excluded after the screening of titles and abstracts. Of the 190 remaining studies, 72 studies (40 082 biopsies) 2,3,9,14,25-92 were included in the systematic review and meta-analysis after full-text review (Figure 1) including 4 single-center randomized controlled trials, 3 multicenter cohort studies (1 mixed retrospective-prospective and 2 retrospective), and 65 single-center cohort studies (10 prospective, 1 mixed retrospective-prospective, 46 retrospective, and 8 unreported). Details of the included studies are presented in Table S1, SDC, http://links.lww.com/TP/C332.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 5004 unique records were identified, of which 4814 records were excluded after the screening of titles and abstracts. Of the 190 remaining studies, 72 studies (40 082 biopsies) 2,3,9,14,25-92 were included in the systematic review and meta-analysis after full-text review (Figure 1) including 4 single-center randomized controlled trials, 3 multicenter cohort studies (1 mixed retrospective-prospective and 2 retrospective), and 65 single-center cohort studies (10 prospective, 1 mixed retrospective-prospective, 46 retrospective, and 8 unreported). Details of the included studies are presented in Table S1, SDC, http://links.lww.com/TP/C332.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet function analyzer-100 (PFA-100) test measures activated platelets and is more sensitive in comparison with the bleeding time for bleeding disorders. However, it was not found to be useful in predicting bleeding post kidney biopsy [25,26].…”
Section: Introductionmentioning
confidence: 94%
“…All studies were observational cohort studies, and only two were prospective in nature. 18,20 The definition used for aspirin exposure was disparate. While some studies limited valid aspirin exposure to a confirmed dose the same day as the kidney biopsy, others had broader criteria that included patients with any confirmed dose within 10 days of the intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…1,[3][4][5][6] Despite advancements in the technique and equipment, major hemorrhagic complications are still responsible for lengthier hospital stays and increased treatment costs, 6,7 occurring in 0.24%-6.6% of all patients subjected to kidney biopsies. 2,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Various factors have been associated with increased biopsy complication rates, including unmodifiable factors, such as age and sex, comorbidities (high serum creatinine levels, obesity, anemia, systemic autoimmune diseases, amyloidosis), and procedure-associated aspects. 2,[5][6][7]10,[23][24][25] Most centers have similar safety requirements, with universal consensus regarding the need for adequate blood pressure control and correction of any preexisting coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation